Age Estimation by the Morphometric Analysis of Sternal End of Fourth Rib - Aditi Bhatnagar; Nirupma Gupta; Rachna Rohatgi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Estimating the age at death in the adult skeleton is problematic owing to the biological variability in ageindictors and the differential skeletal response to environmental factors over an individual’s life. While thepubic symphysis and intracortical morphometry have provided successful results in estimating age at death,other methods and sites in the skeleton are needed to improve the accuracy of age estimation. Present studyis an attempt to develop a new method for estimation of age from sternal end of fourth rib. Currently thereare different parameters available to determine the age of a person like study of teeth, ossification of bonesand other ancillary data, but the accurate reliability of these measures is only limited to a particular agegroup i.e. 25± 5 years. For the age beyond this, many workers in different parts of the world have done theirstudies to accurately determine the age of a person from the skeleton. A random study of 100 cases for ageestimation from sternal ends of the fourth ribs were carried out to estimate the age after death with minimalerror.